2022
DOI: 10.1017/dmp.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Biosafety Measures in Clinical Setting During the COVID-19 Pandemic: A Cross-Sectional Study With Brazilian Dental Students

Abstract: Objective: To evaluate the knowledge of Brazilian dental students about biosafety measures that should be adopted in the clinical setting during the coronavirus disease-2019 (COVID-19) pandemic. Methods: A cross-sectional study with 1,050 dental students was conducted. A semi-structured questionnaire was shared with students. Mean knowledge score on biosafety guidelines during the COVID-19 pandemic was the outcome, with a maximum of 8 scores. Explanatory variables included sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 50 publications
2
11
0
1
Order By: Relevance
“…health epidemiology. The instrument was not validated, but all items on the questionnaire were pilot‐tested with a group of undergraduate dental students at two public universities in Brazil; details of this process can be found in previous studies 28,29 . The questionnaire containing the variables of interest was constructed in thematic blocks/steps, as follows: Sociodemographic characteristics; Institutional profile of students and actions of dental schools regarding the maintenance of curricular activities at the beginning of the COVID‐19 pandemic; Caretaking responsibilities and environmental conditions for the maintenance of distance learning during the pandemic; Feelings/perceptions of anxiety, fear and concerns about the impact of the pandemic on dental education as well as the risk of contagion and transmission of the COVID‐19 virus in the dental setting; History of testing for COVID‐19; Symptoms of anxiety (GAD). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…health epidemiology. The instrument was not validated, but all items on the questionnaire were pilot‐tested with a group of undergraduate dental students at two public universities in Brazil; details of this process can be found in previous studies 28,29 . The questionnaire containing the variables of interest was constructed in thematic blocks/steps, as follows: Sociodemographic characteristics; Institutional profile of students and actions of dental schools regarding the maintenance of curricular activities at the beginning of the COVID‐19 pandemic; Caretaking responsibilities and environmental conditions for the maintenance of distance learning during the pandemic; Feelings/perceptions of anxiety, fear and concerns about the impact of the pandemic on dental education as well as the risk of contagion and transmission of the COVID‐19 virus in the dental setting; History of testing for COVID‐19; Symptoms of anxiety (GAD). …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the literature has shown that most Brazilian dental students do not have a satisfactory level of basic knowledge on the biosafety measures that should be adopted in the dental setting during the COVID-19 pandemic. 28 The importance of training and updating biosafety protocols for dental care during the pandemic in order to reduce anxiety among Brazilian dental students was reported in a previous investigation. 62 The lack of an adequate working environment and more concise information on biosafety may increase the occurrence of anxious behaviour among students who offer patient support during the pandemic.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 95%
See 2 more Smart Citations
“…[23][24][25][26][27][28][29][30][31][32][33] Therefore, personal safety of medical personnel is important for prevention and control. [34][35][36][37][38][39][40][41][42][43][44][45] According to the relevant documents, guidelines and other materials and the working experience of the designated hospital, and in combination with the current situation of the existing sites, equipment, facilities and personnel of the Department, the corresponding prevention, and control plan is formulated. [46,47] From the perspective of the laboratory, this paper discusses how to do a good job in biosafety protection, improve biosafety protection measures, and optimize the workflow.…”
Section: Introductionmentioning
confidence: 99%